Massless charged wormhole solution in Einstein-Maxwell-Scalar theory - Mazharimousavi, S. Habib (Springer, 2022)
A new exact wormhole solution in Einstein-Maxwell-Scalar theory is introduced. The wormhole solution is accompanied by a non-black hole naked singular branch solution. Both of the solutions are massless such that with charge zero the spacetime coincides with the vacuum Minkowski flat spacetime. In addition to that, the wormhole solution seems to be the missing part of the class of solutions in the standard Einstein-Maxwell-Dilaton theory with an arbitrary dilaton parameter.
Keywords: Dilaton Black-Holes; Energy; Field; Gravity